2014
DOI: 10.1007/s00128-014-1270-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Metals, Hematology and Hepatic Enzyme Activities in Lactating Cows Reared in the Vicinity of a Lead–Zinc Smelter

Abstract: The present study examines blood metals levels and health parameters in dairy cows reared in areas around a Pb-Zn industrial complex located near the city of Zanjan-Iran. Blood samples (n = 27) were collected from cows reared around the smelter. Blood samples (n = 25) were also collected from cows reared in areas where chances of Pb contamination of soil, water and fodder do not exist, to serve as reference. The mean blood Pb level in cows around the smelter (1.09 ± 0.26 µg/mL) was higher than the cows from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
8
11
1
Order By: Relevance
“…Exposure of lead affects hepatic drug metabolizing enzymes and cholesterol metabolism, produces oxidative stress, antioxidant imbalance, hepatic necrosis and hyperplasia suggesting a potential role of lead in hepatic damage (Ait Hamadouche et al, 2014). Several reports explained the elevated levels of plasma hepatic and muscle function enzymes due to arsenic and lead exposure in cattle and mice (El-Nekeety et al 2009 andMohajeri et al, 2014). Several studies noticed increased plasma glucose, total cholesterol, triglycerides with decreased plasma protein and albumin in lead exposed cattle and mice (El-Nekeety et al, 2009 andMohajeri et al, 2014) which were in line with the results of the present study.…”
Section: Thyroid and Adrenal Functionsupporting
confidence: 92%
See 2 more Smart Citations
“…Exposure of lead affects hepatic drug metabolizing enzymes and cholesterol metabolism, produces oxidative stress, antioxidant imbalance, hepatic necrosis and hyperplasia suggesting a potential role of lead in hepatic damage (Ait Hamadouche et al, 2014). Several reports explained the elevated levels of plasma hepatic and muscle function enzymes due to arsenic and lead exposure in cattle and mice (El-Nekeety et al 2009 andMohajeri et al, 2014). Several studies noticed increased plasma glucose, total cholesterol, triglycerides with decreased plasma protein and albumin in lead exposed cattle and mice (El-Nekeety et al, 2009 andMohajeri et al, 2014) which were in line with the results of the present study.…”
Section: Thyroid and Adrenal Functionsupporting
confidence: 92%
“…Normal level of lead in healthy bovine blood is 0.04-0.24µg/ ml (Kaneko et al 1997). lead level in animals reared around industrial units is mainly through contaminated drinking water and fodder (Mohajeri et al, 2014). The present findings of higher lead level in drinking water, soil and fodder samples collected from lead contaminated area of Ludhiana might be due to higher lead emission from nearby industrial units contaminating the water, soil and fodder; which in turn may be the reason for high blood lead level in buffaloes in this study.…”
Section: (B) (A) Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, based on the standard deviation observed in this study, we can suggest a higher heterogeneity of milk heavy metal contamination within areas than between areas. This was expected as the contamination of milk by heavy metals is mainly due to contamination of the environment and also the contamination of fodder given to the dairy cows (Mohajeri et al, 2014;Shailaja et al, 2014). For instance, the proximity of lead zinc factories favoured contamination (Mohajeri et al, 2014;Patra et al, 2008;Swarup et al, 2005).…”
Section: Pb (μG/l)mentioning
confidence: 96%
“…This was expected as the contamination of milk by heavy metals is mainly due to contamination of the environment and also the contamination of fodder given to the dairy cows (Mohajeri et al, 2014;Shailaja et al, 2014). For instance, the proximity of lead zinc factories favoured contamination (Mohajeri et al, 2014;Patra et al, 2008;Swarup et al, 2005). These last authors found that the mean blood Pb level in cows around the smelter was higher (1.09 ± 0.26 mg/L) than the cows from the reference area (0.72 ± 0.25 mg/L).…”
Section: Pb (μG/l)mentioning
confidence: 97%